Cumhuriyet'in 100. Yılında 100 Türk Yazar - Tuğluk, Abdulhakim; Kalsın, Şirvan; Karaca, Nesrin; Arıkan, Seda; Özyön, Arzu; Yılmaz, Nusret; Doğan, Nur; Taştan, Zeki; Yavuz, Mehmet Cihan; Özher, Sema; Kılıçarslan, Veli; Mengi, Nesrin; et al. (2024)
-